No blame no gain? From a No Blame Culture to a responsibility culture in medicine - Joshua Parker; Davies, B (Wiley, 2020)
Healthcare systems need to consider not only how to prevent error, but how to respond to errors when they occur. In the United Kingdom’s National Health Service, one strand of this latter response is the ‘No Blame Culture’, which draws attention from individuals and towards systems in the process of understanding an error. Defences of the No Blame Culture typically fail to distinguish between blaming someone and holding them responsible. This article argues for a ‘responsibility culture’, where healthcare professionals are held responsible in cases of foreseeable and avoidable errors. We demonstrate how healthcare professionals can justifiably be held responsible for their errors even though they work in challenging circumstances. We then review the idea of ‘responsibility without blame’, applying this to cases of error in healthcare. Sensitive to the undesirable effects of blaming healthcare professionals and to the moral significance of holding individuals accountable, we argue that a responsibility culture has significant advantages over a No Blame Culture due to its capacity to enhance patient safety and support medical professionals in learning from their mistakes, while also recognising and validating the legitimate sense of responsibility that many medical professionals feel following avoidable error, and motivating medical professionals to report errors.